Nanobiosensors for early detection of neurodegenerative disease - Fazlali, Paria; Mahdian, Aida; Soheilifar, Mohammad Sina; Amininasab, Seyed Mojtaba; Shafiee, Parisa; Wani, Irshad Ahmad; AL-Mokaram, Ali M.A. Abdul Amir (Journal of Composites and Compounds, 2022)
Early detection of neurodegeneration-related disorders that emerge as people age, is critical for both the disease's treatment and the patient's living conditions. Parkinson's and Alzheimer's illnesses are two well-known instances of neurodegeneration, which are characterized by nerve cell death and dementia. The fact is that some illnesses are only diagnosed clinically after symptoms develop hinders therapy. The biomarkers detection, which are unique chemicals found in bodily fluids and are implicated in neurodegenerative processes, may assist in the early detection of neurodegenerative illnesses. Recent years have seen a surge in interest in biosensor research, with the goal of detecting possible biomarkers of the neurodegenerative process with appropriate precision. Biosensors' main purpose is to identify a specific material with high specificity. This manuscript reviews neuro-biosensors for the prognosis of neurodegenerative illnesses like Parkinson's disease (PD) and Alzheimer's disease (AD), as well as a summary of the field's urgent needs, highlighting the critical importance of early detection along the neurodegeneration pathway in general. This study examines biosensor systems designed to identify biomarkers of neurodegenerative diseases (NDDs), with an emphasis on the last five years.